Two Contemporary Russian Novellas - Allan, Helen (LiNQ (Literature in North Queensland), 2016)
Valentin Rasputin, Money For Maria. Brisbane: University of Queensland Press, 1981. Cloth $14.95 374 pp. Two brilliant novellas, Money for Maria and Borrowed Time by Valentin Rasputin, have recently been translated and published together under the first title. These two pastoral sketches remind us once more that not all the great Russian writers are dead. Rasputin, born in 1937 in a small Siberian village, is proof of that. A disciple of Dostoevsky and Bunin, he writes in the best tradition and style of these authors. Like them, he has a profound feeling for the ancient Russian village way of life, deeply rooted as it was in the soil. Himself of peasant origin, he knows peasants, animals, woods and fields intimately and depicts his rural comedies, tragedies and tragi-comedies with, I think, a somewhat lighter touch than that of our own Thomas Hardy, but reminiscently of Hardy in verity and power. Rasputin takes a decidedly less poetic approach than Hardy, but he is of course writing in far less poetic times.